Faktor-Faktor yang Mempengaruhi Lama Kebuntingan pada Sapi Hissar Sumbawa - Arman, Chairusyuhur (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2006)
A study of factors affecting gestation period was made by statistically analyzing the data relating to 38 calvings of Hissar cattle in BPT & HMT Serading Sumbawa. The average length of gestation period was found to be 289.87 ± 6.42 for all calves, 289.38 ± 6.48 days for males dan 290.71 ± 6.24 for females. Females calves were carried 1.33 days longer than males, the difference, however, tended not to be significant. Calvings were distributed throughout the year, the percentage of calvings was lower (28.95%) during wet season than that of dry season (71.05%). The percentage of calvings both in males and  females  were  found  to  be  higher  during  dry  than  wet  seasons.  It  is  concluded, therefore, that sex does not appear to influence gestation period, while season of calving was found to be responsible in causing variation in the length of gestation period.